Obesity and perceived work discrimination in Spain. Issue 36 (2nd August 2018) - Vallejo-Torres, Laura; Morris, Stephen; Lopez-Valcarcel, Beatriz G.
ABSTRACT: Obesity is increasingly becoming a source of discrimination in many domains of living, including at the workplace. In this study, we estimate obesity-related discrimination in work settings in Spain and explore its potential sources. We use data from the European Health Interview Survey conducted in 2009–2010. Our models control for a comprehensive set of demographic, socioeconomic, health, and work-related sickness characteristics. We run separate models for women and men, and stratify by type of occupation and by area obesity prevalence. Our results indicate that weight-related discrimination in work settings in Spain is concentrated among women with morbid obesity, particularly among those working in customer-facing jobs and living in areas with low-obesity prevalence. These findings emphasize the persistence of the gendered nature of obesity-related discrimination, and provide evidence of a form of induced statistical discrimination. Employers' expectations of lower returns from obese workers in customer facing jobs might be driven by customers' preferences caused by social stigma. Furthermore, the role of area-obesity prevalence highlights the impact of cultural social norms even within the same country.